Humor in Times of COVID-19 in Spain: Viewing Coronavirus Through Memes Disseminated via WhatsApp - Cancelas-Ouviña, Lucía-Pilar (Frontiers in Psychology, 2021)
The COVID-19 crisis, and its ensuing periods of confinement, has generated high levels of social stress on a global scale. In Spain, citizens were isolated in their homes and were not able to interact physically with family members, friends or co-workers. Different resources were employed to face this new stressful and unexpected situation (fitness, reading, painting, meditation, mindfulness, dancing, listening to music, playing instruments, cooking, etc.). Humor was one of the most frequent and widely used strategies in an attempt to keep perspective, deal with the seriousness of the situation and make the day-to-day more bearable. Humor is cultural: it varies from one country to the next and is part of the idiosyncrasies of a culture. It is deemed a particularly important feature of the Spanish personality. During the COVID-19 crisis, the main means or channels of communication were social networks. Throughout the confinement period, there was an excessive flow of humorous memes concerning Coronavirus and related shared experiences during the National State of Emergency decreed by the Spanish Government. The memes draw on irony, ingenuity and creativity to make a difficult and stressful experience more bearable. In this paper, a qualitative methodology based on ethnography research is used and ethnographic fieldwork is carried out on the memes disseminated through WhatsApp during the lockdown period experienced in Spain (14 March to 21 June 2020). The memes are considered to be an example of Netlore, digital contemporary folklore, and a theoretical framework on memes and humor is presented that discusses its different functions in order to channel grief, fear and suffering or to play down specific situations. A corpus of 644 memes that have flooded social networks are categorized and analyzed to witness how the Spanish have managed to bring out their humorous and creative side in difficult times even as they have criticized political decisions, let out their frustrations, described their new “normal” lives, interacted with others and anticipated the future.